Regular exercise and branched‐chain amino acids prevent ischemic acute kidney injury‐related muscle wasting in mice - Soichiro Nagata; Akihiko Kato; Shinsuke Isobe; Tomoyuki Fujikura; Naro Ohashi; Hiroaki Miyajima; Hideo Yasuda (Physiological Reports, 2020)
Abstract Acute kidney injury (AKI) causes glucose and protein metabolism abnormalities that result in muscle wasting, thereby affecting the long‐term prognosis of critical illness survivors. Here, we examined whether early intervention with treadmill exercise and branched‐chain amino acids (BCAA) can prevent AKI‐related muscle wasting and reduced physical performance in mice. Unilateral 15 min ischemia‐reperfusion injury was induced in contralateral nephrectomized mice, and muscle histological and physiological changes were assessed and compared with those of pair‐fed control mice, since AKI causes severe anorexia. Mice exercised for 30 min each day and received oral BCAA for 7 days after AKI insult. By day 7, ischemic AKI significantly decreased wet weight, myofiber cross‐sectional area, and central mitochondrial volume density of the anterior tibialis muscle, and significantly reduced maximal exercise time. Regular exercise and BCAA prevented AKI‐related muscle wasting and low physical performance by suppressing myostatin and atrogin‐1 mRNA upregulation, and restoring reduced phosphorylated Akt and PGC‐1α mRNA expression in the muscle. Ischemic AKI induces muscle wasting by accelerating muscle protein degradation and reducing protein synthesis; however, we found that regular exercise and BCAA prevented AKI‐related muscle wasting without worsening kidney damage, suggesting that early rehabilitation with nutritional support could prevent AKI‐related muscle wasting.